2007
DOI: 10.1182/blood.v110.11.1469.1469
|View full text |Cite
|
Sign up to set email alerts
|

Improved Leukemia-Free and Overall Survival in Patients with Myelodysplastic Syndrome Receiving Iron Chelation Therapy: A Subgroup Analysis.

Abstract: Myelodysplastic syndrome (MDS) is characterized by ineffective hematopoiesis and risk of progression to acute myeloid leukemia (AML). Many MDS patients (pts) require red blood cell (RBC) transfusions, risking iron overload (IOL)-related organ dysfunction. We previously showed in a multivariate analysis of 178 pts, improved survival in 18 pts with low and int-1 IPSS risk MDS and IOL receiving iron chelation therapy (ICT), and now examine the effect of ICT on AML-free survival (LFS). The effect of ICT on cytopen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…35 Furthermore, Sanz et al identified serum ferritin >1000 ng/mL as a strong predictor of shorter leukemia-free survival, 25 whereas a subgroup analysis of 18 patients with low-risk or intermediate-1 risk MDS who were treated with deferoxamine demonstrated significantly improved leukemia-free survival (median not reached at 226 months compared with 40 months for a matched control). 62…”
Section: Impact Of Iron Overload On Survivalmentioning
confidence: 99%
“…35 Furthermore, Sanz et al identified serum ferritin >1000 ng/mL as a strong predictor of shorter leukemia-free survival, 25 whereas a subgroup analysis of 18 patients with low-risk or intermediate-1 risk MDS who were treated with deferoxamine demonstrated significantly improved leukemia-free survival (median not reached at 226 months compared with 40 months for a matched control). 62…”
Section: Impact Of Iron Overload On Survivalmentioning
confidence: 99%
“…In a subsequently reported subgroup analysis, the 18 chelated patients again showed better survival than matched control patients, but the control patients were significantly older, and no deaths in their group could be linked with iron overload. 24 Rose et al analysed, by multivariate analysis, survival and cause of death in 97 low-or intermediate-1 risk transfusion-dependent patients. 25 Patients receiving ICT were younger with lower IPSS.…”
Section: Iron Chelation Results In Clinically Relevant Improvements Imentioning
confidence: 96%
“…The results are open to selection bias of favourable patients to the ICT group. In a subsequently reported subgroup analysis, the 18 chelated patients again showed better survival than matched control patients, but the control patients were significantly older, and no deaths in their group could be linked with iron overload 24 …”
Section: Guideline Assumptionsmentioning
confidence: 92%